Correlation Between Oral Health and Systemic Inflammation (COHESION): A Randomized Pilot Follow-Up Trial of a Plaque-Identifying Toothpaste - Acharya, Amit; Glurich, Ingrid; Hetzel, Scott; Kim, KyungMann; Tattersall, Matthew C.; DeMets, David L.; Hennekens, Charles H. (The American journal of medicine, 2020)
Inflammation is intimately involved in the pathogenesis of atherosclerosis and is accurately measured by high-sensitivity C-reactive protein (hs-CRP), a sensitive marker for future risk of cardiovascular disease. The Correlation between Oral Health and Systemic Inflammation (COHESION) trial was designed to test the hypothesis that PlaqueHD, a plaque-identifying toothpaste, reduces hs-CRP. The trial was designed initially to include 132 subjects with hs-CRP between 2.0 and 10.0 mg/L but instead randomized 112 between 0.5 and 10.0, of which 103 had baseline and follow-up data and comprised the intention-to-treat sample. Of these, a prespecified subgroup analysis included 40 with baseline hs-CRP >2.0 and all hs-CRP <10. Because the distribution of hs-CRP was skewed toward higher values, to achieve normality assumptions, the significance of changes in hs-CRP between groups over time was tested on log-transformed data using a mixed effects analysis of variance. The intention-to-treat analysis showed no significant differences between the PlaqueHD and placebo group (P = .615). The prespecified subgroup analysis showed a significant difference between the PlaqueHD and placebo group (P = .047). Results of the analysis showed a reduction in hs-CRP at follow-up of 0.58 in the PlaqueHD and an increase of 0.55 in the placebo group. These findings are compatible with those of a prior pilot trial that also suggested benefits only in subjects with baseline elevations. Future trials targeting reductions of hs-CRP levels should randomize subjects with baseline hs-CRP between 2.0 and 10.0 mg/L.